Shock tube measurements of high-temperature argon broadening and shift parameters for the potassium D1 and D2 resonance transitions. (November 2021) - Ding, Yiming; Vandervort, Joshua A.; Strand, Christopher L.; Hanson, Ronald K.
Highlights: Used KCl as a precursor for generation of high-temperature K vapor in a shock tube. Measured absorption profiles for the K D1 and D2 transitions in the near-infrared. Modeled the high-temperature line shape data as Voigt profiles. Reported K-Ar collisional broadening and shift coefficients between 1100 and 1900 K. The presented method is readily deployable for other gases and alkali metals. Abstract: The current study presents a novel approach to determine the spectroscopic line shape parameters of atomic potassium in a controlled laboratory environment and reports the results for temperatures between 1100 – 1900 K. Experiments were conducted in a shock tube using argon as the dilution gas. Potassium was introduced through a precursor, potassium chloride salt, on the surface of a stainless-steel threaded-rod inserted upstream of the measurement plane. The incident shock wave entrained the potassium chloride in the test gas before the reflected shock wave dissociated the compound, producing atomic potassium at ppb levels for spectroscopic studies with tunable diode lasers. This potassium seeding approach was tested over a wide range of temperatures and is readily deployable for other collisional partners and for other absorbing species of alkali metals. The well-resolved absorption features of both the potassium D1 and D2 transitions near 0.77  μ m were modeled as Voigt profiles, enabling high-fidelity calculations of the argon broadening coefficients and pressure shift coefficients at various temperatures. The results are presented as temperature-dependent power-law expressions. These correlations will be useful for interpretation of brown dwarf spectra and for the development of remote sensing techniques in high-enthalpy facilities.